2020
DOI: 10.1007/s00170-020-05985-5
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the effects of the process parameters of hydro-mechanical deep drawing on manufacturing high-quality bimetallic spherical-conical cups

Abstract: This paper aims to analytically, experimentally, and numerically study the hydro-mechanical deep drawing (HMDD) process of bimetallic specimens. The blank included aluminum and steel sheets used to produce double-layer conical-spherical cups. The punch geometry, maximum fluid pressure, pre-bulge pressure, layer arrangement, and the drawing depth were the process parameters investigated in this article. Two criterions based on the thickness strain and thickness variation were used to assess the effects of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The schematic representation of the Conventional Deep Drawing process and the main hydroforming processes can be seen in Figure 1 [11,12]. Several differences regarding the tools used, contact conditions, and forming technology among the presented processes are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The schematic representation of the Conventional Deep Drawing process and the main hydroforming processes can be seen in Figure 1 [11,12]. Several differences regarding the tools used, contact conditions, and forming technology among the presented processes are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Yaghoubi et.al in their study found that the quality and consistency of the final double-layer product were improved by applying an optimized value of fluid pressure of 15 MPa to the underside of the workpiece. The bending and tensile stresses at the punch tip were more consistently distributed in the presence of this amount of pressure, and the level of thinning was significantly reduced when compared to the usual deep drawing technique [26]. Furthermore, Jalil et al [27] provided a theoretical model for calculating the critical rupture pressure in the manufacturing of double-layered conical pieces using a hydrodynamic deep drawing process with radial pressure as a helper.…”
Section: Introductionmentioning
confidence: 99%
“…The main objectives of their research were to reduce the forming force and improve the thickness distribution. Yaghoubi and Fereshteh-Saniee [11] studied the effect of uid pressure and pre-bulge pressure in the HMDD process to produce aluminumsteel bimetallic specimens. The results of their research showed a remarkable improvement in uniformity of the nal product in the presence of appropriate uid and pre-bulge pressures.…”
Section: Introductionmentioning
confidence: 99%